2016
DOI: 10.1007/s00204-016-1833-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural uranium on the UMR-106 osteoblastic cell line: impairment of the autophagic process as an underlying mechanism of uranium toxicity

Abstract: Natural uranium (U), which is present in our environment, exerts a chemical toxicity, particularly in bone where it accumulates. Generally, U is found at oxidation state +VI in its oxocationic form [Formula: see text] in aqueous media. Although U(VI) has been reported to induce cell death in osteoblasts, the cells in charge of bone formation, the molecular mechanism for U(VI) effects in these cells remains poorly understood. The objective of our study was to explore U(VI) effect at doses ranging from 5 to 600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…A remarkable and very recent example of toxicological study supported by XAS is offered by Pierrefite-Carle and collaborators [54]. The primary sites of uranyl ions {U(VI)O 2 } 2+ (U(VI) for simplicity) accumulation are bones, where a permanent storage takes place potentially leading to a long term toxicity.…”
Section: Speciation Of Toxic Elementsmentioning
confidence: 99%
“…A remarkable and very recent example of toxicological study supported by XAS is offered by Pierrefite-Carle and collaborators [54]. The primary sites of uranyl ions {U(VI)O 2 } 2+ (U(VI) for simplicity) accumulation are bones, where a permanent storage takes place potentially leading to a long term toxicity.…”
Section: Speciation Of Toxic Elementsmentioning
confidence: 99%
“…Furthermore, it is very likely also mediated by bone cells. 53,54 An instantaneous fixation by bone mineral such as what is observed with NCA-ref-young sample would lead to a much higher fraction in the skeleton.…”
Section: Solid/liquid Exchange In the Presence Of U(vi)mentioning
confidence: 96%
“…We performed a cellular correlative microscopy approach by coupling SXRF imaging to epifluorescence microscopy for the identification of organelles and/or proteins fluorescently labeled (Roudeau et al, 2014;Carmona et al, 2019;Das et al, 2019). Previous studies using transmission electron microscopy (TEM) indicated that after acute exposure to high uranium concentrations (> 300 µM) of alveolar macrophages, renal, or bone cells, uranium precipitates forming large needle-shape structures within cytoplasmic vesicles such as lysosomes (Hengé-Napoli et al, 1996;Mirto et al, 1999;Carrière et al, 2008;Pierrefite-Carle et al, 2017). We thus designed our study in order to evaluate, at lower non-cytotoxic concentration, the possible uranium co-localization with the cellular vesicular pathway (early endosomes, late endosomes, and lysosomes).…”
Section: Introductionmentioning
confidence: 99%